Affective factors during field research that influence intention to persist in the geosciences. Issue 2 (2nd April 2020) - Kortz, Karen M.; Cardace, Dawn; Savage, Brian
Abstract: Although field and research experiences have been shown to help retain students in the geosciences, there is less known about how and why this is the case. We created a field-based research experience for five students with a range of backgrounds and prior experiences. We used mixed methods case study research to identify affect-related persistence factors influencing geoscience interns during a field-based research experience, to interpret how the experience elicited those factors, and to explain why the factors influenced students' intention to persist. The study is framed within the Social Cognitive Career Theory and Geoscience Identity theoretical frameworks. Results indicate that the students in this field-research experience were influenced by five main factors: increasing self-efficacy, discovering people as resources, developing a geoscience identity, making connections with Earth, and maintaining interest. The first three factors have important social aspects to them that were impacted by the design of the field experience. The field experience contributed, positively or negatively, to the students developing the self-efficacy to succeed as a geoscientist and the geoscience identity needed to pursue a geoscience career. Therefore, these affective reactions of the students to the field experience, rather than cognitive reactions, played a key role with regard to impacting their intention to major in the geosciences.